3-(x-1)=x+2

Simple and best practice solution for 3-(x-1)=x+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3-(x-1)=x+2 equation:


Simplifying
3 + -1(x + -1) = x + 2

Reorder the terms:
3 + -1(-1 + x) = x + 2
3 + (-1 * -1 + x * -1) = x + 2
3 + (1 + -1x) = x + 2

Combine like terms: 3 + 1 = 4
4 + -1x = x + 2

Reorder the terms:
4 + -1x = 2 + x

Solving
4 + -1x = 2 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
4 + -1x + -1x = 2 + x + -1x

Combine like terms: -1x + -1x = -2x
4 + -2x = 2 + x + -1x

Combine like terms: x + -1x = 0
4 + -2x = 2 + 0
4 + -2x = 2

Add '-4' to each side of the equation.
4 + -4 + -2x = 2 + -4

Combine like terms: 4 + -4 = 0
0 + -2x = 2 + -4
-2x = 2 + -4

Combine like terms: 2 + -4 = -2
-2x = -2

Divide each side by '-2'.
x = 1

Simplifying
x = 1

See similar equations:

| 12-3x=8x+2 | | 4+8x+25-5y=23 | | 103-7x=11x+23 | | 5-(x-7)=x-4 | | 7-7x=57-21x | | X^3-6x^2+8x-2=0 | | 11x+3=2(5x-1)+5 | | 0=2x-16 | | 0.4x+4.4=3.8 | | 0=-x+15 | | o=-x+15 | | 10-2(2-x)=18 | | x+4+3+x-2+x^2+2x+3x-4=30 | | (x+7)(x+9)=2x+62 | | 20x^3-6x=0 | | (x+2)*x=80 | | 4x^2-y^2-40x-14y+15=0 | | 2x+3-4=2x-1 | | 81-3x=24x+18 | | -69-9x=9x+21 | | 122-5x=4x+15 | | 0=-2x-4 | | 6n+18=6 | | (x+2)*x=8 | | (D^3+4D^2-3D-18)y=0 | | 0.4x+4.5=0.3x+2.5 | | 6a-6+4a=4a+24 | | p+6.5p=27 | | -12=6x-8x-22 | | 7(3-0.5k)=3k-5 | | .625y-7=3 | | 5(5-12)-24=3(s+2) |

Equations solver categories